The concept and practice of a football training program: An understanding in the transition period - Fitri Agung Nanda; Japhet Ndayisenga; Sumarno Sumarno (Sepakbola, 2022)
The football competition period lasts 6-9 months on an annual training program. Long competitions certainly result in physical and mental fatigue in athletes. In the theory of training periodization, a period of rest after the end of the competition (transition period) gives athletes the opportunity to rest and psychic relaxation while maintaining optimal physical condition. This paper seeks to review the literature relevant to the concepts and practices in the transition period. Discussion covers two main things: the facts that occur during the transition period and exercises that athletes need to do during the transition period. The results of this discussion aim to make athletes and coaches understand the things that occur during the transition period and what exercise practices, such as what athletes need to do to prevent the potential detraining syndrome. So that in the preparation period of the new season, the athlete's performance level is in good condition.